2008
DOI: 10.1086/524106
|View full text |Cite
|
Sign up to set email alerts
|

On the Fraction of Quasars with Outflows

Abstract: Outflows from active galactic nuclei (AGNs) seem to be common and are thought to be important from a variety of perspectives: as an agent of chemical enhancement of the interstellar and intergalactic media, as an agent of angular momentum removal from the accreting central engine, and as an agent limiting star formation in starbursting systems by blowing out gas and dust from the host galaxy. To understand these processes, we must determine what fraction of AGNs feature outflows and understand what forms they … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
179
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(195 citation statements)
references
References 59 publications
14
179
0
2
Order By: Relevance
“…This supports previous suggestions that at least some narrower and broader absorption phenomena are physically related (e.g., Arav et al 1999;Gallagher et al 2002;Ganguly & Brotherton 2008;Misawa et al 2008). Flatter hard X-ray spectra observed for QSOs with mini-BAL and especially BAL absorption could be explained by ionized or partial-covering absorber models with high (N H 10 22 cm −2 ) effective column densities.…”
Section: Are Mini-bals Just Narrow Bals?supporting
confidence: 89%
See 1 more Smart Citation
“…This supports previous suggestions that at least some narrower and broader absorption phenomena are physically related (e.g., Arav et al 1999;Gallagher et al 2002;Ganguly & Brotherton 2008;Misawa et al 2008). Flatter hard X-ray spectra observed for QSOs with mini-BAL and especially BAL absorption could be explained by ionized or partial-covering absorber models with high (N H 10 22 cm −2 ) effective column densities.…”
Section: Are Mini-bals Just Narrow Bals?supporting
confidence: 89%
“…The velocity-width distinction used to classify absorbers as BALs (width > 2000 km s −1 ), mini-BALs (intermediate widths), and narrow absorption lines (NALs; width < 500 km s −1 for C iv) is somewhat arbitrary; it has been suggested that BAL absorption is an extension of the same physical processes responsible for narrower absorption features observed in QSO spectra (e.g., Section 4.2.1 of Arav et al 1999;Ganguly & Brotherton 2008). Previous studies of BAL QSOs have found that their UV absorption properties are correlated with the relative X-ray brightness of these sources (e.g., Gallagher et al 2006), indicating a physical link between X-ray absorption and the acceleration of BAL outflows.…”
Section: A Continuum Of Absorber Properties?mentioning
confidence: 99%
“…The doublet Mg + λλ2796,2803 is a low ionization line (LIL) that has long been thought to be produced in a dense optically thick region where at least part of the Balmer lines arise (Grandi & Phillips 1979;Netzer 1980). A possible complication is that Mgiiλ2800 is a resonance line and therefore often affected by broad (Ganguly & Brotherton 2008) and narrow absorption (Wild et al 2008). Several authors have attempted to define a relation between Mgiiλ2800 and Hβ to provide consistent M BH estimates from the two lines A89, page 2 of 16 (McLure & Jarvis 2002;Wang et al 2009;Shen & Liu 2012;Trakhtenbrot & Netzer 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many AGNs show blueshifted absorption from outflowing matter (Ganguly & Brotherton 2008). Very broad absorption lines (BALs) corresponding to a wide variety of velocities are observed in luminous quasars.…”
Section: Introductionmentioning
confidence: 99%